BUSINESS PLANNING AT BUMDES SARI LUYU WARNASARI VILLAGE PANGALENGAN DISTRICT, BANDUNG REGENCY - Trisa Nur Kania; Latifah Adnani (Universitas Pasundan, 2021)
The purpose of this research is to analyze the Sari Luyu Village-Owned Enterprise that has been running for 5 years, but does not yet have an independent business because all the business units it works are carried out through business partnerships with villagers who already have a business. Its business activities include: selling melon gas cylinders, beef cattle farms, 2 units of rafting boat rentals, rental of wedding party equipment and circumcision rentals. In the early 2020, BUMDes management Sari Luyu and Warnasari Village Head had thought about the need to start a business unit that would be managed directly by the BUMDes management, which would establish a BUMDes stall which would be located next to the Warnasari village office building. The main factor that caused the emergence of the business idea was because in the village office area there were already potential potential customers, namely community members who came for treatment at the puskesmas and community members who had an interest in the village office as well as a number of people who worked at the Warnasari village office. Another supporting factor is the presence of students in the Warnasari public elementary school, where the location of the school building is right in front of the village office. The research method used was a case study with interviews as technical data collection to informants and non-participant observation as well as literature study. Data analysis uses data credibility, transferability, dependability and confirmability tests. The plan to open a BUMDes stall is expected to further strengthen the position of BUMDes as a reliable business entity in gaining profits for BUMDes because the location is relatively far from other stalls owned by villagers.